Math for all season. Mind stretching math riddles - Tang, Greg; local (New York: Scholastic Press, 2002)
"Math For All Seasons is the second in a series of books that teaches problem-solving to children. I wrote it for a younger audience (ages 5-8) than The Grapes of Math, but it shares the same goal of encouraging kids to think through problems rather than rely on memorization. In terms of computational skills, I hope this book will help kids make a smoother transition from counting to arithmetic by introducing intuitive ways to group and add numbers. It also teaches kids to be open-
Each problem has a little twist, Each verse a clue you might have missed. So try a riddle on for size, Your brain will like the exercise. And when you're done it will be clear, That math's a blast throughout the year!
minded and practical, and encourages strategic thinking that is rooted in common sense."
Keywords: K-3; sears; sears; sears; sears; sears; sears